The natural Art. Artists of diferent species. - Cabeça, Paulo (2022)
Edgar Morin (1975) stated that “Society is one of the most widely spread fundamental forms,developed in avery unequal but very varied way. “It is concluded that neither communication, nor the symbol, nor the rite, are human exclusives. And that they have very remote roots in the evolution of species.” Since Karl von Frisch discovered in the 1920s that bees use the dance movement to communicate the spatial locations of resources among honeycomb companions, symbolic language has ceased to be an exclusive advance of humans (A. Gentile. 2021).